The Philosophy of Education in the Sultanate of Oman: Between Perennialism and Progressivism - Kooli, Chokri; Zidi, Chiraz; Jamrah, Ahmad (American Journal of Education and Learning, 2019)
Using a descriptive analytical method, this research will provide a critical examination of the Sultanate of Oman philosophy of education. The purpose of this research is to present and analyze the main attributes of the philosophy of education in the Sultanate of Oman. An investigation of the government’s educational orientations is performed through linking the different attributes observed in its philosophy of education to the five following main philosophies of education: Perennialism, Essentialism, Progressivism, Existentialism, and Social Reconstructionism. The data analysis showed that the most viewed educational philosophical dispositions were progressivism and Perennialism. In fact, Oman’s Philosophy of education combines openness to the world values and preservation of the Arab-Muslim national culture and values. The study also found that the Sultanate of Oman has developed an educational philosophy that draws its background from national and universal values. It also contains the main guidelines that educative institutions and instructors must follow. Despite the fact that this philosophy seems to be instructors centered, it shows openness and internationalization of the standards of education.